Elucidation of the Formation Mechanism of 2-Mercapto-3-Methyl-1-Butanol in Beer. Part II: Identification of the Key Enzymes in Yeast. (5th December 2020) - Noba, Shigekuni; Kikuchi, Kaori; Kato, Taku; Kusunoki, Keizo; Toyota, Saki; Kobayashi, Minoru; Uemura, Kazuhiko; Nishiyama, Makoto
Abstract: 2-Mercapto-3-methyl-1-butanol (2M3MB) imparts an onion-like off-flavor to beer and is known to be formed from 2, 3-epoxy-3-methylbutanal (EMB), which is generated in the reaction of iso-alpha acids with oxygen during the hot aeration of brewer's wort. Our previous results revealed that 2-mercapto-3-hydroxy-3-methylbutanal (2M3H3MB), formed from EMB by a nonenzymatic reaction with hydrogen sulfide, serves as the intermediate to 2M3MB. However, little is known regarding the 2M3H3MB to 2M3MB conversion process. In the present study, preparative column chromatography coupled with an enzyme assay revealed that two enzymes of Saccharomyces pastorianus, Old Yellow Enzyme 2 (Oye2p) and alcohol dehydrogenase 6 (Adh6p), are involved in the conversion process. An in vitro reaction containing these enzymes purified from recombinant Escherichia coli cells converted 2M3H3MB to 2M3MB. Furthermore, a yeast mutant with deletion of the genes encoding these two enzymes dramatically decreased 2M3MB formation. Our series of studies has therefore revealed the overall mechanism of 2M3MB formation starting from EMB through 2M3MB.